2002
DOI: 10.1046/j.1537-2995.2002.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Motivations to donate blood: demographic comparisons

Abstract: WB donations appear to be made primarily for altruistic reasons and in response to appeals for blood. Ways to build on this humanitarianism and take advantage of new communication routes, such as e-mail, need to be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
252
3
17

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(305 citation statements)
references
References 22 publications
(40 reference statements)
28
252
3
17
Order By: Relevance
“…Recent efforts have been made by blood collection agencies to shorten the health history and make repeat donation a faster process [14]. Similar to previous results, most of our study participants did not believe any recognition was necessary [15,16]. Some suggested that a thank you or feedback on how their donation aided another individual would be helpful.…”
Section: Discussionsupporting
confidence: 81%
“…Recent efforts have been made by blood collection agencies to shorten the health history and make repeat donation a faster process [14]. Similar to previous results, most of our study participants did not believe any recognition was necessary [15,16]. Some suggested that a thank you or feedback on how their donation aided another individual would be helpful.…”
Section: Discussionsupporting
confidence: 81%
“…We developed donor motivation scales based on a priori hypotheses guided by previously tested questions among blood donors (Glynn et al 2002;Sharma et al 2001) and corroborated by factor analysis. Three scales for donor motivation were identified: altruism, self-interest, and direct appeal.…”
Section: Resultsmentioning
confidence: 99%
“…After providing written informed consent, donors completed the self-administered, structured Portuguese questionnaire including approximately 30 items adapted from a previous survey of blood donors (Glynn et al 2002;Sharma et al 2001). The instrument included demographic characteristics, reasons for blood donation, HIV/AIDS knowledge, and behavioral risk factors for HIV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relativo aos fatores intrínsecos que conduzem os sujeitos à doação de sangue, partindo do entendimento de que o desenvolvimento de um comportamento de doador exige do indivíduo uma postura de envolvimento social que pode ser representada por uma conduta altruísta e empática 22,24,25,26,27 , e voltada para atender as necessidades dos outros, foi possível definir as três hipóteses a seguir: H2 -O altruísmo influencia positivamente a predisposição para doar sangue. H3 -A empatia influencia positivamente a predisposição para doar sangue.…”
Section: Fatores Motivacionais Da Doação De Sangueunclassified